Hubungan Pengendalian Intern dan Kompensasi dengan Kecurangan Akuntansi ( Studi pada BPR di Provinsi Lampung ) - Aminah AMINAH; Chindy Yolanda Faramitha (Universitas Bandar Lampung (UBL), 2016)
In this study used quantitative analysis method, which samples used were obtained from the questionnaire data (questionnaire). Method of quantitative analysis in general is a method that is more emphasis on the objective measurement of the social phenomena. To be able to perform measurements, every social phenomenon translated into several components of the problem, variables and indicators. Each variable is determined at the measurement by providing symbols figures vary according to the categories of information relating to these variables. Formulation of the problem in this research is